Obstructed femoral hernia with an associated De Garengeot hernia - Zukiwskyj, Marianna; Michael C. Auld (International Surgery Journal, 2023)
A De Garengeot hernia is the eponymous name to describe a femoral hernia containing the appendix. Imaging may confirm the diagnosis pre-operatively; however, many are identified at the time of surgery. We describe the case of an elderley female patient who presented with a small bowel obtruction due to an incarcerated femoral hernia, with the unexpected finding at the time of surgery of the appendix additionally within the hernia. Following diagnostic laparoscopy, she underwent a laparoscopic appendicectomy and open suture repair of the femoral hernia.